Pembuatan Tepung Umbi Porang (Amorphophallus oncophyllus) Berkualitas Tinggi Sebagai Bahan Baku Ekstraksi Glukomanan - Mutia Amyranti; Ismi Nurlatifah (Politeknik ATI Padang, 2022)
One of Indonesia's forest products is porang tubers (Amorphophallus Oncophyllus). Porang tuber is a food plant that has a potential source of glucomannan. Post-harvest processing is one of the main problems in obtaining optimal glucomannan levels in porang tubers. This study aims to obtain high quality porang tuber flour by increasing the glucomannan content in porang tuber flour. The research method used was the soaking technique on porang tuber chips before being processed into porang flour. The solvent (anti-browning agent) used as an immersion in this study was sodium metabisulfite with a concentration of 2%, 5% and 7.5% and ascorbic acid with a concentration of 2%, 5% and 7.5%. The length of immersion time in this study was 3 hours (30, 60, 90, 120, 150 and 180 minutes). The results showed that the immersion technique carried out tend to have a real effect on increasing glucomannan levels. The best glucomannan content obtained was in the immersion treatment using sodium metabisulfite at a concentration of 7.5% with an immersion time of 180 minutes of 88.20% and the immersion treatment using ascorbic acid at a concentration of 5% with an immersion time of 150 minutes of 79.45%. The best characteristics of porang tuber flour from the results of the analysis showed the contents of water, protein, fat, carbohydrates and ash respectively were 12.758%, 7.039%, 0.926%, 73.111% and 0.988%.The soaking process using an anti-browning agent can increase glucomannan content as an increase in the selling value of porang flour.